Care and support model for health care providers of HIV and AIDS patients in the public hospitals of Limpopo Province - Moshidi, Maria Lebeko (My University, 2018)
Introduction: Health care workers have a pivotal role in the management of Human Immune Deficiency Virus (HIV) and Acquired Immune Deficiency Syndrome (AIDS) and their well-being is consequently crucial as it could impact negatively on the quality of caregiving. With the development of a care and support model, the needs of health care workers can be identified and catered for, and quality patient care will be rendered through well-cared and supported health care workers. Purpose: The purpose of this study was to develop a care and support model for health care providers of patients diagnosed with HIV and AIDS in the public hospitals of the Limpopo Province. A key step in the development of a model for care and support is to explore and describe the experiences of professional nurses regarding care and support they receive while providing care to HIV and AIDS patients in the public hospitals of Limpopo Province Methods: A qualitative, descriptive, exploratory and contextual design was the method used which guided the development of the model. The population of the study were the professional nurses in five public hospitals from each district of the Limpopo Province. These hospitals were selected because they all shared similar characteristics of having clinics where HIV and AIDS patients receive care. The sample was purposively selected. The sample size was 20 professional nurses which was determined by data saturation, meaning that four professional nurses who worked for 24 months or more per public hospital were selected. Data were collected through face-to-face interviews and an audiotape was used to record all unstructured interview sessions conducted. Analysis of data were done through using an open-coding method in accordance with Tech’s qualitative data methodology to develop a model. Results: The research findings revealed emotional and physical strain due to shortage of staff and heavy workload which was exacerbated by staff turnover and high absenteeism. Exhaustion, fatigue, development of work-related vi illnesses and increased level of stress were also challenges experienced which led to increased customer complaints and decreased quality of service provided to patients. Many professional nurses were not trained in the management of patients with HIV and AIDS, but were expected to execute their activities competently. There was also lack of counselling, debriefing sessions, recognition and rewarding systems for the health professionals who were taking care of those patients. Recommendations: This Care and Support Model provides strategies to be used by the managers in public hospitals of Limpopo Province to enhance care and support to health care providers of HIV and AIDS patients. The model should be implemented at various public hospitals throughout Limpopo Province and feedback provided so that it could be further developed and refined. Conclusion: The results indicated that health care providers of HIV and AIDS patients were deprived of the necessary care and support during provision of care to HIV and AIDS patients. A model for care and support as a strategy to assist the managers to offer care and support to health care providers of HIV and AIDS has been developed. The model is a contribution to the nursing management, the government and it serves as a guideline for improving the quality of patient care through well-cared and supported health care workers.
Thesis (Ph.D. (Nursing Science)) -- University of Limpopo, 2018
Keywords: Care and support model; Health care provider; HIV/AIDS patient; Professional nurse; HIV-positive persons; HIV-positive persons -- Care -- South Africa -- Limpopo; AIDS (Disease) -- Patients; Medical personnel